Processo de implantação de um modelo de gestão em grupos semi-autônomos: O caso michelin - De Oliveira Archanjo De Souza, Daniele Santos; Oliveira, Adriana Leônidas; Muniz Jr., Jorge [UNESP] (My University, 2010)
Searching by the productivity increase, the institutions have applied several concepts related to persons and processes. However in some cases, these concepts are introduced and kept so misappropriated. In this context, many authors recognize the competitive advantage of working with models of participative management that allow whatever it takes to the man to exercise their intellectual abilities and provide better working atmosphere. Thus, this article presents significant factors in the implementation of a management model - Organization with Responsibility - which aims to the exercise of autonomy by the employees and result in greater speed in the responses effectively to the requirements of flexibility and other market requirements. To achieve this research, the scope was limited to production area of the tire industry of the Southern Region state of Rio de Janeiro - at Michelin. This choice is justified because of the economic importance and its analogy with the standards industry studied in this search connected to strategic management of human resources with the models of work organization: the semi-autonomous work groups. Based on a quantitative and qualitative analysis of the data, was evaluated the operators satisfaction after the implementation of the new model and then discussed the actions that could be held to consolidate the same.
Process of implantation of a management semi-autonomous work group model: The case michelin
Keywords: Management with operational participation; Semi-autonomous work group; Strategical management of human resources; Work organization